Bauhäusler on the Franco-Spanish Border - Martínez de Guereñu, Laura (The Open Library Of Humanities, 2016)
This article focuses on the travels of Bauhaus masters and instructors and on the transport of Bauhaus products to Spain in 1929, when the Franco-Spanish border was still culturally permeable. Ludwig Mies van der Rohe and Marcel Breuer introduced their tubular-steel furniture in the Spanish market. Mies and Lilly Reich designed the interiors of all German industrial sections at the Barcelona International Exposition, where the Bauhaus sent objects from its carpentry, metal, and weaving workshops. Josef and Anni Albers traveled to see the exhibition and then went to meet Vassily Kandinsky and Paul Klee, who spent over a month on holiday in the Côte Basque. Albers captured their trip in photo collages, Kandinsky registered his impressions in snapshots, while Klee wrote abundant correspondence and produced drawings. Focusing on the itineraries the Bauhäusler followed, along with the means by which they expressed their travel impressions, this article reveals the effect of travel in their later design attitudes and work. Significant cultural transfers between Germany and Spain took place in a critical moment of European history, suggesting that further developments of these learning experiences might have materialized later on both sides of the border, possibly even reaching across the Atlantic.Fundación BBVA- Convocatoria 2015 de Ayudas a Investigadores y Creadores Culturales Bauhaus, España, América: Intercambios y Transferencias culturales (1928-1975)